(untitled) (Applied Biological Research, 2025)
The use of natural carotenoids in fish-feed to intensify the colouration is a sustainable and cost-effective choice for ornamental fish farmers to meet the demand of radiant ornamental fish within budget.Onion (Allium cepa) peel powder in formulated feed was used to restore natural colour in Indian rosy barb (Pethia conchonius) fish. A basal diet was prepared by using fishmeal, soybean meal, groundnut oil cake, rice bran, wheat flour, starch powder, soya oil, and vitamins & minerals. Experimental diets were prepared by replacing equivalent rice bran with onion peel powder at three concentrations viz., 5% (D1), 10% (D2), and 15% (D3) of the basal diet (D0).The feeding trial was conducted for 60 days. At the end of the feeding trial, a significant increase in total carotenoids concentration (4.3 ± 0.2 μg g⁻¹; p < 0.05) and weight gain (35.17%) was observed in rosy barb of D2 (10%) diet. All the tanks showed 100% fish survival.The result revealed that 10% inclusion of onion peel powder in the diet of Indian rosy barb can give a fruitful impact on restoration and retention of rosy barb’s natural colour in home aquaria.